2018
DOI: 10.1134/s1995425518040030
|View full text |Cite
|
Sign up to set email alerts
|

Climatic Response of Conifer Radial Growth in Forest-Steppes of South Siberia: Comparison of Three Approaches

Abstract: We compared three approaches to study climatic signals of Pinus sylvestris and Larix sibirica tree-ring width chronologies from the forest-steppe zone of South Siberia, where both temperature and precipitation limit the conifer tree growth: 1) paired correlation of chronologies with monthly climatic variables; 2) paired and partial correlations with monthly and seasonal series of primary and secondary climatic factors, calculated in the Seascorr program; 3) paired correlation with a 15-day moving average serie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 54 publications
(52 reference statements)
1
4
0
Order By: Relevance
“…Most boreal spruce forests have showed negative growth trends as the climate warmed, which has been interpreted as a response to temperature-induced drought stress, particularly in the southern Eurasia taiga [48]. Several studies have reported a dominant role of summer water availability to tree growth in the southern and middle taiga [23,[49][50][51][52]. Our findings agree with these observations since the growth of the study stands was constrained by warm and dry June to July conditions.…”
Section: Discussionsupporting
confidence: 89%
“…Most boreal spruce forests have showed negative growth trends as the climate warmed, which has been interpreted as a response to temperature-induced drought stress, particularly in the southern Eurasia taiga [48]. Several studies have reported a dominant role of summer water availability to tree growth in the southern and middle taiga [23,[49][50][51][52]. Our findings agree with these observations since the growth of the study stands was constrained by warm and dry June to July conditions.…”
Section: Discussionsupporting
confidence: 89%
“…These series have the same length of 65 years (1951-2015) as the original daily data, which should ensure sufficient reliability of the revealed patterns in the climatic signal. A similar approach with windows of 10-25 days has already been used to analyze the climatic signal in chronologies not only of TRW, but also of other wood structure parameters (Helama and Sutinen 2016;Carrer et al, 2017;Castagneri et al, 2017;Belokopytova et al 2018).…”
Section: Climatic Datamentioning
confidence: 99%
“…Clarification of the most significant period influencing by climate on tree growth using daily climatic series and the moving periods of their generalization was carried out in previous research (Belokopytova et al, 2018). The results demonstrated that climate can vary significantly between remote sites within the region due to climatic gradients even when their habitat conditions are homogeneous.…”
Section: Discussionmentioning
confidence: 98%